Rural livelihoods in Mon state, Myanmar: Evidence from a representative household survey - Hein, Aung; Htoo, Kyan; Kham, L. Seng; Win, Myat Thida; Thinzar, Aye Mya; Naing, Zaw Min; Thida, Mi Win; Lei, Ni; Min, Lu; Mwee, Naw Eh; Oo, Zaw; Filipski, Mateusz J.; et al. (Michigan State University, 2018)
The purpose of this report is to provide information and analysis to government, civil society, and donors interested in improving the well-being of the rural population of Mon State. Specifically, the report analyzes the different sources of income for rural households, as well as their socioeconomic characteristics, with a view to identifying potential pathways to improving incomes, especially for poor households, and stimulating inclusive rural growth. The overall picture that emerges is one of an economy heavily dependent on services for local employment and on international migration for income. Like a two-legged stool, such an economy is potentially unstable in the face of external shocks. Diversification of the Mon State economy, including diversification and increased productivity within the agricultural sector, will lessen the relative dependence on external migration remittances and result in more resilient growth in the future.